Large potential of strengthening the land carbon sink in China through anthropogenic interventions - Yue, Xu; Zhou, Hao; Cao, Yang; Liao, Hong; Lu, Xiaofei; Yu, Zhen; Yuan, Wenping; Liu, Zhu; Lei, Yadong; Sitch, Stephen; Knauer, Jürgen; Wang, Huijun (Science bulletin, 2024)
[Display omitted] The terrestrial ecosystem in China mitigates 21%–45% of the national contemporary fossil fuel CO2 emissions every year. Maintaining and strengthening the land carbon sink is essential for reaching China’s target of carbon neutrality. However, this sink is subject to large uncertainties due to the joint impacts of climate change, air pollution, and human activities. Here, we explore the potential of strengthening land carbon sink in China through anthropogenic interventions, including forestation, ozone reduction, and litter removal, taking advantage of a well-validated dynamic vegetation model and meteorological forcings from 16 climate models. Without anthropogenic interventions, considering Shared Socioeconomic Pathways (SSP) scenarios, the land sink is projected to be 0.26–0.56 Pg C a−1 at 2060, to which climate change contributes 0.06–0.13 Pg C a−1 and CO2 fertilization contributes 0.08–0.44 Pg C a−1 with the stronger effects for higher emission scenarios. With anthropogenic interventions, under a close-to-neutral emission scenario (SSP1-2.6), the land sink becomes 0.47–0.57 Pg C a−1 at 2060, including the contributions of 0.12 Pg C a−1 by conservative forestation, 0.07 Pg C a−1 by ozone pollution control, and 0.06–0.16 Pg C a−1 by 20% litter removal over planted forest. This sink can mitigate 90%–110% of the residue anthropogenic carbon emissions in 2060, providing a solid foundation for the carbon neutrality in China.